Koordinasi Tim Operator Sekolah Dalam Penanganan Cyberbullying Diplatform Whatsapp Melalui Manajemen Teknologi Informasi Pada Sekolah Menengah Atas Negeri Klakah, Lumajang - Dayanti, Widya Isma; Nur Ittihadatul Ummah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study examines the coordination of school operator teams in addressing cyberbullying occurring on the WhatsApp platform through the implementation of information technology (IT) management at SMA Negeri Klakah, Lumajang. The rapid development of digital communication has facilitated school administration and strengthened internal collaboration, yet also increased the risk of harmful online behaviors among students. This research aims to analyze how IT management supports the coordination process among operators, teachers, guidance counselors, and school leadership in preventing and responding to cyberbullying cases. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving key informants such as the principal, student affairs personnel, school operators, and student representatives from OSIS and MPK. The findings reveal that coordination is carried out systematically through communication pathways that integrate digital supervision, reporting procedures, and preventive education. The IT management system supported by digital data platforms, internal communication channels, and school standard operating procedures plays a significant role in enhancing monitoring and ensuring responsible digital behavior among students. The study also highlights the importance of religious and ethical values, particularly responsibility, honesty, and cooperation, in shaping a safe and respectful digital culture. Overall, the research concludes that effective IT management strengthens the coordination of school operator teams and contributes to creating a secure, ethical, and well-managed digital environment within the school community.